Effects of demineralization on the stable isotope analysis of bone samples - Tomaszewicz, Calandra Turner (Rapid Commun Mass Spectrom, 2015)
RATIONALE: The sampling of sequential, annually formed bone growth layers for stable carbon (δ(13)C values) and nitrogen (δ(15)N values) isotope analysis (SIA) can provide a time series of foraging ecology data. To date, no standard protocol exists for the pre-SIA treatment of cortical samples taken from fresh, modern, bones. METHODS: Based on the SIA of historical bone, it is assumed that fresh bone samples must be pre-treated with acid prior to SIA. Using an elemental analyzer coupled to an isotope ratio mass spectrometer to measure stable carbon and nitrogen ratios, we tested the need to acidify cortical bone powder with 0.25M HCl prior to SIA to isolate bone collagen for the determination of δ(13)C and δ(15)N values. We also examined the need for lipid extraction to remove potential biases related to δ(13)C analysis, based on a C:N ratio threshold of 3.5. RESULTS: It was found that acidification of micromilled cortical bone samples from marine turtles does not affect their δ(15)N values, and the small effect acidification has on δ(13)C values can be mathematically corrected for, thus eliminating the need for pre-SIA acidification of cortical bone. The lipid content of the cortical bone samples was low, as measured by their C:N ratios, indicating that lipid extracting cortical bone samples from modern marine turtles is unnecessary. CONCLUSIONS: We present a standard protocol for testing fresh, modern cortical bone samples prior to SIA, facilitating direct comparison of future studies. Based on the results obtained from marine turtle bones, pre-acidification and lipid removal of cortical bone are not recommended. This is especially useful as there is frequently not enough bone material removed via micromilling of sequential growth layers to accommodate both acid treatment and SIA.